Measurements of WW and WZ production in W+jets final states in pp̄ collisions - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Aoki, M.; Askew, A.; et al. (American Physical Society (APS), 2012)
We study WW and WZ production with νqq (=e,μ) final states using data collected by the D0 detector at the Fermilab Tevatron Collider corresponding to 4.3fb -1 of integrated luminosity from pp̄ collisions at √s=1.96TeV. Assuming the ratio between the production cross sections σ(WW) and σ(WZ) as predicted by the standard model, we measure the total WV (V=W,Z) cross section to be σ(WV)=19.6-3.0+3.2pb and reject the background-only hypothesis at a level of 7.9 standard deviations. We also use b-jet discrimination to separate the WZ component from the dominant WW component. Simultaneously fitting WW and WZ contributions, we measure σ(WW)=15.9-3.2+3.7pb and σ(WZ)=3.3-3.3+4.1pb, which is consistent with the standard model predictions. © 2012 American Physical Society.